PENGEMBANGAN TINDAK BAHASA TERAPI DALAM INTERVENSI ANAK AUTIS SPEKTRUM PERILAKU - Luluk Sri A. Prasetyoningsih (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2016)
This study aims to develop a prototype of therapeutic language acts for the intervention in children with behavioral spectrum autism. This was a research and development studyemploying the R2D2 (Recursive, Reflective, Design, and Development) model. It consistedof product design, product validation, tryout, product revision, and mass production.The prototype of therapeutic language acts was collaboratively developed by involvingthe developer, expert team (a language expert and a clinical expert), and practitioner (atherapist). The data were collected through observations, field notes, and questionnaires.The results show that the developed prototype of therapeutic language acts satisfies thecriteria for accuracy, utility, and appropriateness. The conclusion is that the prototypeof therapeutic language acts for the intervention in children with behavioral spectrumautism satisfies the criteria for acceptability and can be used as a reference to deal withchildren with behavioral disorder autism.